Recent Developments in Rare Ovarian Carcinosarcoma: Literature Review and Case Report - Alexandra Nienhaus; Elena Bernad (Diseases, 2025)
Background and Objectives: Ovarian carcinosarcoma (OCS) is a rare gynecologic malignancy defined by both epithelial and mesenchymal components, generally associated with advanced clinical stage and poor outcomes. We present a 66-year-old patient initially presenting with right iliac vein thrombosis, ultimately diagnosed with OCS, and place these findings in context with a focused literature review from 2000 through to 2024. Methods: A comprehensive account of the patient’s clinical course—spanning diagnostic imaging, surgical pathology, neoadjuvant chemotherapy, and interval debulking—was combined with a review of the current data on OCS pathogenesis, treatment protocols, and outcomes. Results: The patient’s tumor showed predominantly sarcomatous histology (approximately 90%) with high-grade serous features, responded to platinum/taxane chemotherapy, and was resected to no visible residual disease. The updated literature indicates that the majority of OCS cases present at advanced stages (often exceeding 60%), with suboptimal cytoreduction closely tied to worse prognosis. Up to 64% of tumors may harbor homologous recombination deficiency, offering a rationale for PARP inhibitor therapy; nonetheless, five-year survival rarely surpasses 45% in most series. Conclusions: Despite its aggressive course, optimal debulking surgery plus platinum-based chemotherapy remain central in treating OCS. Emerging molecular insights highlight homologous recombination deficiency and BRCA mutations as potential therapeutic targets. Multidisciplinary care and future prospective studies are key to improving long-term outcomes in this challenging malignancy.